Expression of future prospective in indirect speech (Proceedings of Southern Federal University. Philology, 2015)
The article analyzes the characteristics and use of grammatical semantics and lexical and grammatical means used to create future prospects in double indirect discourse. The material for the study were epic works by contemporary German writers. In the analysis of the empirical material it has been pointed out that indirect discourse has preterial basis and is the kind of most frequent inner speech of characters. The most widely used form with future semantics in preterial indirect speech is conditional I, formally having a conjunctive basis, but is mostly used with the indicative semantics. Competitive to conditional I in indirect speech is preterial indicative. A characteristic feature of the indirect speech is the use of modal verbs, which, thanks to its semantics is usually referred as an action at a later term, creating the prospect of future statements. The most frequent were modal verbs wollen and sollen in the form of the preterite, more rare verbs were m ssen and k nnen. German indirect speech distinguishes the ability to use forms on the basis of conjunctive: preterite and plusquamperfect of conjunctive. Both forms express values similar to those of the indicative. However, conjunctive forms the basis of the data shown in a slightly more pronounced seme of uncertainty that accompanies future uses of these forms in indirect speech. In addition, plusquamperfect conjunctive differs from others by the presence of the seme of completeness.Keywords: indirect speech, future, konditsionalis I, preterit indicative, modal verbs, preterit and plusquamperfect conjunctive.Bodnaruk Elena Vladimirovna - North (Arctic) federal university, Arkhangelsk, Russian Federation. Institute of linguistics and cross-cultural communication, German and French linguistics dpt. Candidate of linguistics, professor assistant. Тел.: 8-911-564-49-07; е-mail: bodnaruk@rambler.ru